Environmental and economic prerequisites of amber mining in Ukraine - Martyn, A.; Kachanovskyi, O. (Land Management, Cadastre and Land Monitoring, 2023)
The negative consequences of illegal amber mining lead to damage to the country’s economy and the destruction of the ecosystem in those regions where intensive mining is conducted. The article is devoted to a comprehensive consideration of the issue of illegal amber mining. The ecological and economic prerequisites for the emergence of the problem of illegal mining are given, and its main ecological, economic and social consequences are also determined. It is argued that the illegal actions of prospectors and their consequences continue to be a painful issue in the socio-economic life of Ukraine, from which not only the natural environment, but also the economy of Ukraine suffers. As a result of the uncontrolled extraction of precious stones, the actions of criminal groups smuggling them abroad, the state will not receive millions of hryvnias from the state budget. The calculation of Ukraine’s annual losses from illegal amber mining and sales is presented. The distribution of reserves and extraction of amber by administrative regions of Ukraine was analyzed. It is noted that there are two direct payments related to amber mining: a fee for a special permit for the development of the site and mining, as well as rent - a share of the income from the sale of precious stones. Generalized data on the formation of amber deposits and mining taxation processes in Lithuania and Poland are provided. The dynamics of selling prices of Ukrainian and Polish amber is presented, a significant drop in the price of Ukrainian raw amber compared to 2016 was established. The problem of illegal mining in forest areas in the north-west of Poland has been studied. It is noted that amber prices are constantly changing depending on the fractions, but the introduction of a single fixed rate will contribute to the development of this industry. Key words: amber mining, disturbed lands, rent, land rehabilitation.